2019
DOI: 10.3389/fnsys.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Entrainment of Prefrontal Cortex Local Field Potential Activity Following Patterned Stimulation of the Cerebellar Vermis

Abstract: The cerebellum is involved in sensorimotor, cognitive, and emotional functions through cerebello-cerebral connectivity. Cerebellar neurostimulation thus likely affects cortical circuits, as has been shown in studies using cerebellar stimulation to treat neurological disorders through modulation of frontal EEG oscillations. Here we studied the effects of different frequencies of cerebellar stimulation on oscillations and coherence in the cerebellum and prefrontal cortex in the urethane-anesthetized rat. Local f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 107 publications
1
3
0
Order By: Relevance
“…Since animal and human research relates theta activity with the septo-hippocampal complex and anterior cingulate cortex, which are important limbic brain structures involved in cognition and emotion, it was speculated that, in addition to the cerebellocortical connections found by previous studies, the cerebellum is part of the core neural limbic circuitry involved in emotions. The findings of both studies are in line with more recent research that has found evidence that cerebellar stimulation can entrain local field potentials in the frontal cortex and drive synchronization of cerebellocortical and cortico-cortical networks (Tremblay et al 2019). Results reported in this study do not only further substantiate the contributions of the medial cerebellum to large-scale synchronization in non-motor-related brain areas, but also provide indirect and incremental support for cerebellar involvement in the experience and regulation of emotions.…”
Section: Cerebellar Transcranial Magnetic Stimulationsupporting
confidence: 91%
“…Since animal and human research relates theta activity with the septo-hippocampal complex and anterior cingulate cortex, which are important limbic brain structures involved in cognition and emotion, it was speculated that, in addition to the cerebellocortical connections found by previous studies, the cerebellum is part of the core neural limbic circuitry involved in emotions. The findings of both studies are in line with more recent research that has found evidence that cerebellar stimulation can entrain local field potentials in the frontal cortex and drive synchronization of cerebellocortical and cortico-cortical networks (Tremblay et al 2019). Results reported in this study do not only further substantiate the contributions of the medial cerebellum to large-scale synchronization in non-motor-related brain areas, but also provide indirect and incremental support for cerebellar involvement in the experience and regulation of emotions.…”
Section: Cerebellar Transcranial Magnetic Stimulationsupporting
confidence: 91%
“…Attention to the role of the cerebellum in seizures and epilepsy is growing in the clinical setting as well as in experimental studies with animal models. For example, there is a greater appreciation that the cerebellum can influence the physiology of neocortical (Popa et al, 2013;Watson et al, 2014;Tremblay et al, 2019) as well as subcortical structures such as the hippocampus via polysynaptic pathways (Yu and Krook-Magnuson, 2015;Bohne et al, 2019;Watson et al, 2019;Zeidler et al, 2020). Neocortical modulation of cerebellar physiology has also been demonstrated (Ros et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we show that stimulation parameters which are effective in one brain state may not be effective, or even have opposite effects, in another brain state. In vitro and in vivo animal models have revealed that the modulatory impact of electrical stimulation is frequency-dependent and timing-dependent [ 21 , 30 , 31 ], but, to our knowledge, this is the first demonstration in human neuromodulation protocols in epilepsy. A state-based view of electrical stimulation paradigms implies that the impact of neurostimulation extends beyond direct seizure termination, consistent with an emerging concept of RNS having long-term neuromodulatory effects [ 32 ] that facilitate transitions from high and low seizure risk states, which may bear an indirect relation to cortical “up” and “down” states.…”
Section: Discussionmentioning
confidence: 99%